REASONS FOR CANADA’S INTERVENTION IN THE CASE OF THE ARRESTED HUMAN RIGHTS ACTIVICT’S IN SAUDI ARABIA IN 2018 - Sitepu, Ribka Agi; Kumala Dewi, Putu Ratih; Widya Nugraha, A.A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2024)
Human Rights, Intervention, Diplomatic Relations, Foreign Policy, Policy Influencer